Características anátomo-estruturais da pelé de ovinos (ovis áries L.) lanados e deslanados, relacionadas com o aspecto físico-mecânico do couro - Jacinto, Manuel Antonio Chagas; Silva Sobrinho, Américo Garcia Da [UNESP]; Costa, Roberto Germano (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2004)
The objective of the study was establishing the anatomical-structural differences between the skin of non-wool sheep of the Morada Nova breed and wool-on sheep of the Polwarth or Ideal breeds and their relations to the physical-mechanical characteristics of their leather after tanning. Ten animals of both breeds were used, with five animals of approximately one and four years of age of each breed. The animals were slaughtered, and immediately after skinning, samples were taken viewing the microtomy of the skin in the dorsal, lateral, ventral, hind and palette regions, parallel and perpendicular to the head-tail axle, and perpendicular to the grain of the skin. The skins were depilated, chromium-tanned and re-tanned. From the leather, three samples were taken from the two directions considered from the regions studied for physical-mechanical analysis, for tension and tear resistance and distension on the lastometer. The average of the results of the physical-mechanical analysis were compared by Tukey test at the levels of 1 and 5% probability. The breed, the age, the region and the position exerted a positive effect on the values of the resistance of the leather to tension for the Morada Nova four year old sheep, reaching a minimum of 200 kg/cm . The region and the position exerted a positive effect on the values of tear-resistence of the leather for both breeds studied, reaching a minimum of 40 kg/cm. The resistance of the leather on distension was superior to 8 mm, for all the animals studied, not influenced by breed, age, region or position. The skin of the Ideal sheep presented a thermostatic skin layer greater than the reticular layer with great folicular and glandular density, contrary to the skin of the Morada Nova sheep where the thermostatic and reticular layers are of approximately the same thickness, with less folicular and glandular density.
Anatomical-structural characteristics of wool-on and non-wool sheep skins related to the physical-mechanic leather aspects
Keywords: Leather; Leather quality; Raw; Skin; Tanning; Animalia; Ovis aries